Characterization of acne patients carrying clindamycin‐resistant Cutibacterium acnes: A Japanese multicenter study. Issue 8 (18th May 2020) - Nakase, Keisuke; Aoki, Sae; Sei, Sayaka; Fukumoto, Sana; Horiuchi, Yuki; Yasuda, Takae; Tanioka, Miki; Sugai, Junichi; Huh, Wook‐Kang Winnie; Kakuta, Mie; Nomoto, Mayumi; Shimada, Tokihiko; et al.
Abstract: Use of antimicrobials for acne treatment is correlated with an increased occurrence of antimicrobial‐resistant Cutibacterium acnes . To clarify the role of antimicrobial use on the resistance and to investigate the characteristics of resistant strains, we conducted a multicenter study in dermatological clinics frequently visited by new patients with acne vulgaris. We collected specimens in 264 acne patients and tested 164 C. acnes strains isolated from 164 patients visiting 13 dermatological clinics. Antimicrobial susceptibility testing showed that the rates of resistance for tetracyclines, macrolides and clindamycin were significantly higher in C. acnes strains isolated from patients using antimicrobials for acne treatment than patients not using them. In particular, clindamycin‐resistant strains were frequently isolated from patients with older median age (≥24 years) and severe/moderate acne. After investigating the resistance mechanism of 15 high‐level clindamycin‐resistant strains, the transposable clindamycin resistance genes, erm (X) or erm (50), were detected in 14 strains. Using single‐locus sequence typing for C. acnes, the strains with erm (X) or multidrug resistance plasmid pTZC1 coding erm (50) and tetracycline resistance gene tet (W) were classified into clade F, which were specifically isolated from Japanese patients with acne, except for one strain. Our data showed that patients' information, such as antimicrobial use, age and acne severity, are valuable in estimating whether a patient carries antimicrobial‐resistant C. acnes . Additionally, our results suggest that the clade F strains have a high risk of acquiring multidrug resistance.